Inovasi Meja Peniris Pentol Guna Mengoptimalkan Proses Pengeringan Pentol dengan Metode Antropometri - Davira, Jendra; Murnawan , Hery (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Drying foods such as pentol is a crucial process in the food industry that affects the quality, safety and shelf life of the product. However, there are still challenges in optimizing this drying process to ensure efficiency and consistency of the final result. In this research, I innovate a bulb draining table that utilizes anthropometric methods to improve the comfort and quality of bulb drying. Anthropometric methods are used to understand the dimensions and characteristics of various bulbs, thereby enabling the design of draining tables that are more appropriate to the needs of the drying process. Apart from that, this innovation also includes the creation of waste collection containers, thereby ensuring hygiene and quality. With this approach, it is hoped that this pentol draining table innovation can increase the efficiency of the drying process, reduce production time and costs, and improve the quality of the final product